A case of tuberculosis in HIV-infected pregnant women - A. V. Nesterenko; V. N. Zimina; I. S. Brekhovа (Журнал инфектологии)
Here is presented the clinical surveillance of course coinfection (and HIV / TB) process of a pregnant woman. In a retrospective discussion of medical tactics marked the main points of contention in the conduct of pregnant women with coinfection (HIV / TB), an analysis of the adequacy and the need for X-ray examination of the patient, the effectiveness of the treatment process coinfection process. The case demonstrates the ability of HIV-infected effectively treat tuberculosis and healthy baby female patient with active tuberculosis with timely and adequate combination therapy (antiretroviral and anti-tuberculosis).